Produção de Quimera de roptria 2 de Neospora caninum com a porção B da toxina termolábil de Escherichia coli enterotoxigênica (rROP²/LTB) como imunobiológico - Santos Junior, Alceu Gonçalves dos (2013)
The intracellular protozoan Neospora caninum, is considered the main causative agent of abortion in cattle. Infection occurs by ingestion of sporulated oocysts in the environment, first occurs systemic parasitemy characterizing acute phase of infection and subsequent chronic phase with formation of tissue cysts, thus persisting the infected and the asymptomatic host. Diagnosis is made by serologic tests. Currently, there are no data to ensure the effectiveness of commercial vaccine available for cattle. Apical complex antigens of the parasite are being studied, since they have an important role in infection. The rhoptries, secretory glands present in this region of the parasite N. caninum, play an important role in invasion and formation of parasitophago vacuoles, these properties have generated interest in its use in experimental vaccine formulations. Experimentally it showed partial results of protection in challenge, when fused to other proteins of this protozoan, the protection was increased, suggesting that antigens fusion is effective for protection against N. caninum. This work produced a new chimeric antigen, originated from the fusion of ROP² N. caninum with the B subunit of heat labile enterotoxin of Escherichia coli. The construction of the chimera was accomplished by cloning in sequence where ROP² gene was inserted directly into the N-terminus of LTB. The construction ROP²/LTB was expressed in E. coli strain BL 21 (DE3) StarTM where it presented a size of approximately 24kDa. The fusion antigen did not impair the antigenicity when tested against positive bovine serum by immunofluorescence, the Western blot technique, therefore, show great potential for use as a recombinant vaccine.